DREPTUL LA VIAȚĂ VERSUS DREPTUL LA MOARTE. CONSIDERAȚII LEGISLATIVE ȘI JURISPRUDENȚIALE PRIVIND LEGALIZAREA EUTANASIEI DIN PERSPECTIVA DREPTURILOR OMULUI (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2022)
The Right to Life Versus The Right to Death. Legislative and Jurisprudential Considerations Regarding the Legalization of Eutanasia from a Human Rights Perspective.The right to life is a fundamental and priority value of the contemporary world, being confirmed by its regulation in the most important international legal instruments. Considering the patient’s right to autonomy, by which he has the right to make decisions about any aspect of treatment, it can be argued that there is also the right to die, by which the patient has the right to demand an end to suffering and to die with dignity. This article aims to analyze the legal aspects of legalizing euthanasia from a human rights perspective, based on eloquent jurisprudence in the field. Advances in recent years in the field of medical and pharmaceutical technologies and which ensures survival, call into question the right to self- determination of patients with incurable diseases. The many concrete cases that stand out through prolonged and unbearable physical and mental suffering have brought up the issue of recognizing a new right - the right to die. Euthanasia is also closely linked to the concept of physician assisted suicide (PAS), in which healthcare professionals provide the means for a patient to suppress his or her own life. Given that advances in medicine have exacerbated the problem of euthanasia or, we can say, highlighted the issue of „dignified death”, this article aims to analyze the regulation of euthanasia at national and global level. This has happened in two directions: towards the technological progress of assistance to the dying and towards the direction of the socialization of medicine.